2018
DOI: 10.1021/acscatal.8b03737
|View full text |Cite
|
Sign up to set email alerts
|

Single Nickel Atoms Anchored on Nitrogen-Doped Graphene as a Highly Active Cocatalyst for Photocatalytic H2 Evolution

Abstract: Earth-abundant nickel is a typical non-noble-metal cocatalyst used for photocatalytic hydrogen evolution (PHE). Ni nanoparticles, however, tend to aggregate during the hydrogen production process, significantly lowering their PHE activity. To avoid aggregation, we used single atom form Ni and anchored them on vacancies in nitrogen-doped graphene (Ni-NG) as a cocatalyst for PHE. We demonstrated that Ni-NG is a robust and highly active cocatalyst for PHE from water. With only 0.0013 wt % of Ni loading, the PHE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(94 citation statements)
references
References 50 publications
3
91
0
Order By: Relevance
“…Recent advances in analytical techniques have enabled the detailed analysis of individual heteroatom dopants in graphitic materials, which allows for identification of the distinctive nature of graphitic- and pyridinic-nitrogen sites 1821 . Various methods have emerged for the preparation of graphitic materials with structural defects surrounded by three pyridinic nitrogens 2224 , paving the way for the introduction of metal cations to impart, e.g., particular catalytic functionality 25,26 with prospective applications in energy conversion 27 and biocompatible catalysis 28 . However, the introduction of structurally defined defects is often random, and precise control over the position of such defects remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in analytical techniques have enabled the detailed analysis of individual heteroatom dopants in graphitic materials, which allows for identification of the distinctive nature of graphitic- and pyridinic-nitrogen sites 1821 . Various methods have emerged for the preparation of graphitic materials with structural defects surrounded by three pyridinic nitrogens 2224 , paving the way for the introduction of metal cations to impart, e.g., particular catalytic functionality 25,26 with prospective applications in energy conversion 27 and biocompatible catalysis 28 . However, the introduction of structurally defined defects is often random, and precise control over the position of such defects remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Recently, lots of Ni-N x catalysts have been reported to support on carbon matrix with different morphologies through various synthetic strategy, including pyrolysis of MOFs [8] or polymeric precursors [9] and postmodification of N-doped graphite materials. [10] Many experiments and theoretical calculations have been made to identify the important role of Ni-N x active sites in CO 2 RR. [11] But the effect of the support geometrical structure of Ni-N x catalysts on CO 2 RR performance has been ignored.…”
Section: Herein a Series Of Carbon Spheres Supported Ni-n 4 Single-amentioning
confidence: 99%
“…Zhao et al reported that Ni could be anchored in N-doped graphene in both SV+3N and DV+4N vacancy centers (SV = single vacancy, DV = double vacancies), forming stable Ni-N 3 and Ni-N 4 active sites with Ni valance at +0.75 and +0.85, respectively, Figure 5. [84] Ni atom in SV-3N center not only showed very low |∆ H G * | for H adsorption on Ni, but reduced the H adsorption |∆ H G * | on N. As a result, the activation energy barrier of HER was notably reduced.…”
Section: Carbon-and C 3 N 4 -Based Sacsmentioning
confidence: 95%